THE CONCEPT OF DEMOGRAPHIC LEXICS (International Conference on Economics, Finance, Banking and Management, 2025)
This article explores the concept of demographic lexics as a specialized terminological system that reflects population processes, structures, and trends. It examines the formation, classification, and evolution of demographic vocabulary across disciplinary boundaries and in different sociocultural contexts. The paper analyzes how demographic lexics both shapes and is shaped by social attitudes toward population issues, highlighting its role in scientific discourse, policy formulation, and public communication about demographic phenomena.